2014
DOI: 10.1080/02705060.2014.907547
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in zooplankton communities in the re-flooded Mesopotamian wetlands, Iraq

Abstract: Non-directional re-flooding of the wetlands in southern Iraq, which were extensively drained during the 1990s, started in 2003. The change in species composition and abundance of rotifer and cladoceran communities together with their abiotic environment were studied for 15 months in the re-flooded wetlands. The re-flooded wetlands were characterized by higher salinity than typical freshwater inland marshes, and some rotifer and cladoceran species were characteristic of the saline, post-reflooding environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The northern section of Shatt Al-Arab River is poorly known in terms of zooplankton taxa. This study indicated that that section has less species of Cladocera (23 species) compared to the Marshes (41 species; Salman et al, 2014). Al-Qarooni (2005) reported only 14 species from the southern Marshes, Ajeel (1998) found 23 species in Shatt Al-Arab River.…”
Section: Discussionmentioning
confidence: 77%
“…The northern section of Shatt Al-Arab River is poorly known in terms of zooplankton taxa. This study indicated that that section has less species of Cladocera (23 species) compared to the Marshes (41 species; Salman et al, 2014). Al-Qarooni (2005) reported only 14 species from the southern Marshes, Ajeel (1998) found 23 species in Shatt Al-Arab River.…”
Section: Discussionmentioning
confidence: 77%
“…The monthly largest numbers of genus were (10 and 9) recorded at station 1, 8 at station 1, and 6 at station 3 in different months of the study, Salman et al (2014) found that rotifera showed monthly changes in genus diversity. Station 1 (Al-Asafia) characterized by a suitable environmental conditions for rotifer to occurs in a high numbers of species and genera compared with the other two stations.…”
Section: Methodsmentioning
confidence: 73%
“…Because of their opportunism and adaptability, rotifers are widely distributed in freshwater planktonic habitats at densities that can exceed 1000 individuals per liter, and if sufficient food is available, occasionally can attain densities from 5000 to >15000 individuals/liter (Gulati et al, 1992;Shao et al, 2001). Ghazi and Ali (2012) investigated the rotifers of Shatt Al-Arab from Qurna to Fao through 12 months and listed 47 taxa and Salman et al (2014) listed 105 species of Rotifera from the Southern Iraqi marshes. Ghazi and Ahmed (2008) studied the abundance and diversity of rotifers in ponds in Garmat Ali region and recorded 26 species.…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted in eastern Al-Hammar marsh, which is located in the southern part of the Euphrates River in Iraq. This marsh extends from Suq Al-Shuyoukh town in Dhi Qar governorate to Basra governorates, its length is 90 km, its width is 25-30 km, and its depth is 3m (Salman et al, 2014), (Fig. 1).…”
Section: Study Areamentioning
confidence: 99%